Neurobiology of Dementia - Minagar, Alireza (International review of neurobiology ;, 2009)
Deals with the various aspects of dementia and provides a wide range of sub-topics in the field of dementia. This monograph intends to stimulate other physicians' and neuroscientists' interest to carry out more research projects into pathogenesis of this devastating group of diseases.